Vocational and Educational Strategies of SVE Students (Based on a Survey in the Murmansk Oblast) - Elena V. Nedoseka; Ekaterina N. Sharova (Арктика и Север, 2022)
The article analyzes the educational and professional strategies of graduates of secondary vocational education (SVE) of the Murmansk Oblast, formed on the basis of prevailing values in the conditions of socialization in a particular region. The paper focuses on the existing contradictions in understanding the reasons for the growth in the number of applicants to secondary vocational institutions. On the basis of statistical data from various sources, an analysis of the system of vocational training at the secondary pro-fessional level is presented and the features of the human resources potential and needs of the region are indicated. The authors of the article focus on environmental factors that contribute to the formation of values and the implementation of vocational and educational strategies for the youth of the region. The theoretical framework of the study is based on the social constructivism theory of P. Berger and T. Lukman, as well as the value theory of R. Inglehart. The object of the study is graduate students in the secondary vocational education system of the Murmansk Oblast. The choice of a specific subject of the Russian Arctic (Murmansk Oblast) is due to a number of reasons: intensive migration loss of the population; significant reduction in the number of educational institutions; reduction in the number of students. The empirical base of the article was formed by the results of a sociological study conducted in AprilMay 2021 in the Murmansk Oblast by online questionnaire survey among graduates of educational institutions of secondary vocational level — 519 people. The study of professional and educational strategies of graduates of secondary vocational education, an analysis of educational plans, attitudes towards employment, including the direction of training, labor value orientations as well as migration attitudes of students were additionally considered.